‘The Intensity, the Passion Can Smoulder beneath the Surface’<subtitle>– Text meets context in Agathe Backer Grøndahl’s romance To the Queen of my Heart</subtitle> - Camilla Hambro (Studia Musicologica Norvegica, 2017)
Abstract This musical analysis of “To the Queen of my Heart” starts out from reception materials connected to Agathe Backer Grøndahl’s and Nina Grieg’s performances of the romance and tries to trace the critics’ descriptions in the score. Focus is directed on how the performed song becomes performative via the reception materials, hers, the listeners’ and amateur performers’ “producerly texts” attached to them. In her interpretation of three different versions of the poem Backer Grøndahl shows her masterly ability to express unspoken, but very important words for thoughts that are not explicitly stated. In this way her romance, in a Mendelssohnian sense, explores the limits of language. On a general level the song’s identification process plays on what the composer, listener or musician places in the voice part. Not only does the voice construct impressions about the poem and the singer’s persona, it also assigns positions for the listener, whether or not s/he chooses to identify with the subject of the song or the object of her/his passion. The romance illustrates the possibility to choose interpretations that stay on good terms with alternative as well as recommended, gendered practice, whether a woman sings it to a man or another woman, or a man sings it to a woman or another man.